Viral hepatitis B and C in HIV-exposed South African infants - Cynthia Tamandjou Tchuem; Mark Fredric Cotton; Etienne Nel; Richard Tedder; Wolfgang Preiser; Avy Violari; Raziya Bobat; Laura Hovind; Lisa Aaron; Grace Montepiedra; Charles Mitchell; Monique Ingrid Andersson (BMC, 2020)
Abstract Background Whilst much attention is given to eliminating HIV mother-to-child transmission (MTCT), little has been done to ensure the same for hepatitis B virus (HBV) transmission. The introduction of HBV immunization at six weeks of age has reduced HBV horizontal transmission in South Africa. However, in order to eliminate HBV MTCT, further interventions are needed. The risk of hepatitis C virus (HCV) MTCT in HIV-infected (HIV+) African women is not yet well described. This study aimed to determine the rate of HBV and HCV vertical transmission in HIV-exposed infants in South Africa. Methods Serum samples from infants enrolled in an isoniazid prevention study (P1041) were screened for HBV and HCV serology markers; screening was performed on samples collected at approximately 60 weeks of age of the infants. HBV DNA was quantified in HBsAg positive samples and HBV strains characterized through gene sequencing. All HCV antibody samples with inconclusive results underwent molecular testing. Results Three of 821 infants were positive for both HBsAg and HBV DNA. All HBV strains belonged to HBV sub-genotype A1. The rtM204I mutation associated with lamivudine resistance was identified in one infant, a second infant harboured the double A1762T/G1764A BCP mutation. Phylogenetic analysis showed clustering between mother and infant viral genomic sequences. Twenty-one of 821 HIV-exposed infants tested had inconclusive HCV antibody results, none were HCV PCR positive. Conclusions This study suggests that HBV vertical transmission is likely to be occurring in HIV-exposed infants in South Africa.. A more robust strategy of HBV prevention, including birth dose vaccination, is required to eradicate HBV MTCT. HCV infection was not detected.